Microclimatic modification of three timber species stands on ex-tin mining land - Koter, Rosdi; Nuruddin, Ahmad Ainuddin (Forestry Department Peninsular Malaysia, 2004)
Establishment of a forest plantation could modify the micro-climate of the area. The main objective of this study was to investigate the effect of three different stands of plantation species on the micro-environment of ex-tin mining land. The study was conducted at Kampung Pasir, Semenyih, Selangor. Three-year-old stand planted were Acacia mangium, Ceiba pentandra and Casuarina equisetifolia, All the stands were planted with Calopogonium mucunoides as cover crop. Environmental parameters such as air temperature, soil temperature, and relative humidity were monitored hourly during the six month study. The results showed that, among the stands Acacia mangium recorded the lowest value for air temperature(24.7°C), soil temperature at 10 cm depth (25.6°C) and 20 cm depth (25.8 °C) but recorded highest value for relative humidity (99%). Open space recorded the highest value of soil temperature (34.7 °C at 10 cm depth; 31.3°C at 20 cm depth) and air temperature (39.5 °C) but showed the lowest value for relative humidity (49%). The results indicated that different stands modified the microclimate differently.